Operational Matrix of Fractional Order Integration and Its Application to Solve Fractional Differential Equations (FDEs) Using Haar Wavelet Collocation Method (HWCM) - Deshi, A. B.; Gudodagi, G. A. (Scientific Inquiry and Review, 2022)
Wavelets play an essential part in numerical analysis. In this study, a novel numerical technique to solve fractional differential equations (FDEs) corresponding to initial conditions is presented using Haar wavelet approximations. Haar wavelet is first presented with an operational matrix of fractional order integration. Then, illustrative examples are presented to signify the validity and applicability of the proposed method.